Training exposure and confidence level among medical officers: Does an Emergency Physician make a difference? - Zakiah, MJ; Nidzwani, MMS; Hanizah, N; Affirul, CA (Societa Editrice Universo, 2024)
Indexed by WOS/ Scopus